Some remarks on the issues of the consequences of war rape on the example of Bosnia and Herzegovina - Czeszejko-Sochacka, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The civil war in Bosnia and Herzegovina was one of the bloodiest armed conflicts after the end of the Second World War. Despite the passage of years, it is still a painful part of reality for a large group of the country's population. During the war, human rights were violated in the form of ethnic cleansing, murders, and so-called genocidal rapes. Women who were raped face social stigma to this day. According to conservative estimates, approx. 4000 children were born as a result of rapes. Today, the adult generation of "children of shame" experiences social ostracism in almost all spheres of life. Their situation is affected by the fact that they are not recognized as "victims of war" under the current regulations. This situation is slowly beginning to change, but it is a long-term process that requires intensified efforts not only in Bosnia and Herzegovina, but also in the international arena.

Wojna domowa w Bośni i Hercegowinie była jednym z najkrwawszych konfliktów zbrojnych po zakończeniu II wojny światowej. Mimo upływu lat nadal jest bolesnym elementem rzeczywistości dla dużej części mieszkańców tego kraju. W czasie wojny dochodziło do łamania praw człowieka w postaci czystek etnicznych, mordów i tzw. ludobójczych gwałtów. Zgwałcone kobiety do dziś spotykają się z napiętnowaniem społecznym. Według ostrożnych szacunków w wyniku gwałtów urodziło się ok. 4000 dzieci. Dziś dorosłe pokolenie „dzieci wstydu” doświadcza ostracyzmu społecznego w niemal wszystkich sferach życia. Na ich sytuację wpływa fakt, że w świetle obowiązujących przepisów nie są uznawani za „ofiary wojny”. Sytuacja ta powoli zaczyna się zmieniać, ale jest to proces długotrwały, wymagający wzmożonych wysiłków nie tylko w Bośni i Hercegowinie, ale także na arenie międzynarodowej.
Keywords: Bosnia and Herzegovina; rapes; crimes against humanity; ICTY; Bośnia i Hercegowina; gwałty; zbrodnie przeciwko ludzkości